2018
DOI: 10.1007/s12094-018-1910-8
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA signatures: aberrantly expressed miRNAs in prostate cancer

Abstract: MicroRNAs (miRNAs) are short, non-coding, conserved, oligonucleotides that are regulatory in nature and are often dysregulated in many cancers including prostate cancer. Depending on the level of complementarity between the miRNA and mRNA target, they can either inhibit translation or degrade the target mRNA. MiRNAs expression is specific to the type of cancer, its stage and level of metastasis, making miRNAs potential stage-specific biomarkers of cancer. Recent research has shown that these miRNAs have the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 179 publications
1
54
0
Order By: Relevance
“…The prognostic potential demonstrated for miMe in the present work corroborate and expand on previous PC studies that have reported prognostic potential for the single miRNAs and DNA methylation candidate markers included in miMe . Due to the marked molecular heterogeneity of PC, prognostic multigene panels may perform better than individual markers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The prognostic potential demonstrated for miMe in the present work corroborate and expand on previous PC studies that have reported prognostic potential for the single miRNAs and DNA methylation candidate markers included in miMe . Due to the marked molecular heterogeneity of PC, prognostic multigene panels may perform better than individual markers.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic potential demonstrated for miMe in the present work corroborate and expand on previous PC studies that have reported prognostic potential for the single miRNAs and DNA methylation candidate markers included in miMe. [6][7][8]10,11 Due to the marked molecular heterogeneity of PC, prognostic multigene panels may perform better than individual markers. Currently, two commercial mRNA-based panels (Prolaris ® and Decipher ® ) are available to help guide post-RP treatment decisions, 21 but the tests are expensive and may not work reliably on FFPE tissue samples where mRNA can be severely degraded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations